Competitive Analysis of Online Grocery Markets in the Baltic States - Kovacova, Irina; Černý, Jan; Molnár, Zdeněk, 1939-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
The aim of this thesis is to offer a comprehensive analysis of the online grocery market in the Baltic States using competitive intelligence practices and tools. The thesis applies the theoretical frameworks of competitive intelligence to analyse basic market dimensions such as market size, market shares, trends and competition. It examines the e-commerce landscape across different periods, including pre-COVID, COVID, and post-COVID eras, and compares the Baltic States' e-commerce development to other regions. The research includes detailed insights into the largest online grocery market players, Barbora and Rimi Baltic, and uses Porter’s Five Forces framework to evaluate industry dynamics. Additionally, it explores differences in logistics, payment options, loyalty programs and website performance between the key players. The study seeks to provide valuable insights for current industry players and newcomers, enhancing comprehension of the evolving online grocery market in the Baltic States.
Vedoucí práce: Jan Černý
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses